Representation of the ‘Other’ in Literature and Popular Culture: A Comparative Study of J.M. Coetzee’s Waiting for the Barbarians and the Television Series Game of Thrones - Kaushik Bhuyan, (Indian Journal of Management and Language (IJML), 2025)
The study of the binaries like the ‘self’ and the ‘other’ has been topic of discussion among various literary and critical theorists. In addition to many others, Postcolonial theorists have always shown a key interest in the study of the binaries like- coloniser and colonised, light and dark, good and bad and so on. Till the twentieth century the Europeans established colonies in the Asian, African and American continents, and this establishment is called ‘colonialism’. However, after the Second World War most of the colonies gained independence, and this gave way to the ‘Postcolonial era’. This end of the colonial order, led to the emergence of the discourse known as ‘Postcolonial’ theory. Postcolonial theory attempts to study the position and representation of the natives during the colonial times. Frantz Fanon, who can be called as one of the earliest Postcolonial theorists, in his The Wretched of the Earth (1961), tried to study the position of the natives in colonial times. With the theorist, many postcolonial writers also tried to portray the colonial world in their works, and one such writer was J M Coetzee. This paper will try to study the presence of the binaries in colonial world through Coetzee’s fictional work Waiting for the Barbarians (1980), by reading it through the insights of Fanon. In addition the paper will also use the medium of popular culture, in the form of the television series Game of Thrones (2011-19) to analyse the binaries outside the colonial context.